2(2n+2)-6(-7)=2n-6n

Simple and best practice solution for 2(2n+2)-6(-7)=2n-6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2n+2)-6(-7)=2n-6n equation:



2(2n+2)-6(-7)=2n-6n
We move all terms to the left:
2(2n+2)-6(-7)-(2n-6n)=0
We add all the numbers together, and all the variables
2(2n+2)-(-4n)-6(-7)=0
We add all the numbers together, and all the variables
2(2n+2)-(-4n)+42=0
We multiply parentheses
4n-(-4n)+4+42=0
We get rid of parentheses
4n+4n+4+42=0
We add all the numbers together, and all the variables
8n+46=0
We move all terms containing n to the left, all other terms to the right
8n=-46
n=-46/8
n=-5+3/4

See similar equations:

| 3y-17+y+40+2y+-5=180 | | 376.65=220+0.65x | | 30x-(10(3x+4)+30=0 | | 3y-17+y+40+2y+-5=90 | | -4u+(1/5)=(-1/5)u-(1/3) | | 72-3y=90 | | 6+10c=256 | | 10-2x-5=3 | | -9f=-10f+18 | | 6x-3=3+4x+9 | | 3(x+1)+3x=-3(x-1)+3 | | 7x÷5x-7=21÷10x | | 9(3n-4)=(8n+8)+1 | | 200+.25m=360 | | 3x+36=9x-24 | | 15=v/13 | | -y-39=19 | | 30+x=-6(10x-5) | | 50x+2=7.50 | | 5.5(2x+11)=-5.5x+63.25 | | 294=14h | | 12x+1+92=25x+2 | | X+x-46+1/2x+x-35=360 | | -20+7c=20+12-6c | | 12x1+92=25x+2 | | 15(2x+2)=10(3x+4 | | -4b-2b=-6b+8 | | 4(5+x)/3=20 | | 1/3t-8=-6 | | 5/8g=3 | | 8x+4x+4x+8=11 | | 72-3y=100 |

Equations solver categories